Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.12938/bmfh.2016-002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Bifidobacterium animalis</i> ssp. <i>lactis</i> GCL2505 on visceral fat accumulation in healthy Japanese adults: a randomized controlled trial

Abstract: Bifidobacterium animalis ssp. lactis GCL2505 (B. lactis GCL2505) is able to survive passage through the intestine and then proliferate, leading to an increase in the amount of gut bifidobacteria. In the present study, we evaluated the impact of B. lactis GCL2505 on abdominal visceral fat storage in overweight and mildly obese Japanese adults. This clinical study was a double-blind, randomized, placebo-controlled, parallel-group comparative trial performed for 12 weeks. Healthy Japanese subjects (N=137) with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 37 publications
2
33
1
Order By: Relevance
“…We identified 1934 records, from which we selected 986 individual abstracts and 161 potentially relevant articles for full review (figure 1). We identified 105 articles19 25–128 reporting data from 99 different research studies including 111 different randomised comparisons of probiotics versus control (further called randomised clinical trials [RCTs], see online supplementary table 1-2) with the following outcomes: BW (number of RCTs: k=58, n=3422 individuals, median=77.4 kg), BMI (k=68, n=4015, 28.2 kg/m²), WC (k=26, n=1583, 98.8 cm); BFM (k=27, n=1562, 27.8 kg), SAT and VAT (k=5, n=543, 192.4 cm² and 114.7 cm², respectively), FG (k=83, n=5188, 6.1 mmol), HbA 1c (k=28, n=1796, 6.3%), INS (k=63, n=3854, 11.0 mU/L), HOMA-IR (k=52, n=3513, 3.2), CRP (k=41, n=2376, 3.6 mg/L), TG (k=74, n=4461, 145.4 mg/dL), ALAT (k=26, n=1466, 38.6 IU/L), ASAT (k=23, n=1340, 36.1 IU/L) and GGT (k=14, n=816, 41.5 IU/L). The median duration of the follow-up was 8 weeks (range: 2–28 weeks), probiotics dose ranged from 10 7 to 10 12 CFU daily, and 43 trials were conducted in one country (Iran).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 1934 records, from which we selected 986 individual abstracts and 161 potentially relevant articles for full review (figure 1). We identified 105 articles19 25–128 reporting data from 99 different research studies including 111 different randomised comparisons of probiotics versus control (further called randomised clinical trials [RCTs], see online supplementary table 1-2) with the following outcomes: BW (number of RCTs: k=58, n=3422 individuals, median=77.4 kg), BMI (k=68, n=4015, 28.2 kg/m²), WC (k=26, n=1583, 98.8 cm); BFM (k=27, n=1562, 27.8 kg), SAT and VAT (k=5, n=543, 192.4 cm² and 114.7 cm², respectively), FG (k=83, n=5188, 6.1 mmol), HbA 1c (k=28, n=1796, 6.3%), INS (k=63, n=3854, 11.0 mU/L), HOMA-IR (k=52, n=3513, 3.2), CRP (k=41, n=2376, 3.6 mg/L), TG (k=74, n=4461, 145.4 mg/dL), ALAT (k=26, n=1466, 38.6 IU/L), ASAT (k=23, n=1340, 36.1 IU/L) and GGT (k=14, n=816, 41.5 IU/L). The median duration of the follow-up was 8 weeks (range: 2–28 weeks), probiotics dose ranged from 10 7 to 10 12 CFU daily, and 43 trials were conducted in one country (Iran).…”
Section: Resultsmentioning
confidence: 99%
“…The mouse gut microbiota is also responsive to increased energy intake, with an increased abundance of Firmicutes and reduced abundance of Bacteroidetes (10)(11)(12). In addition, a number of research groups have reported that the supplementation with prebiotics and/or probiotics tends to increase the abundance of Bifidobacterium in humans and animals (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Many studies have shown beneficial effects with regard to obesity prevention induced by the consumption of certain food ingredients, which is a strategy related to dietary habits [11][12][13]. In addition, probiotics, which constitute a food ingredient, are valuable for obesity prevention and improvement of the gut microbial conditions [14][15][16][17]. Probiotics are defined as "live microorganisms which, when administered in adequate amounts, confer a health benefit on the host" [18], and the modification of the gut microbial composition is one of the main mechanisms underlying the beneficial effects of probiotics on host health [19,20].…”
Section: Introductionmentioning
confidence: 99%